A comprehensive study on compositional and structural changes in 45S5 bioglass products exposed to simulated body fluid. Issue 1 (11th September 2017) - Montinaro, Selena; Desogus, Luca; Orrù, Roberto; Garroni, Sebastiano; Delogu, Francesco; Ricci, Pier Carlo; Cao, Giacomo
Abstract: The interaction of fully dense 45S5‐bioglass derived samples produced by Spark Plasma Sintering (SPS) with simulated body fluid (SBF) solution was investigated in detail taking advantage of the Rietveld refinement method to quantitatively evidence the corresponding microstructural and compositional changes. It is observed that, when the original amorphous nature is mostly (75 wt%) preserved in the material during sintering (550°C, 2 minutes), the resulting specimens dissolve faster and determine relatively higher pH increase and ions release in the SBF solution. Correspondingly, a relatively lower amount of hydroxycarbonate apatite (HCA) is formed on their surface. In contrast, a more extensive apatite layer with trabecular structure is generated within 3 days storage on the surface of fully crystallized samples obtained at 600°C by SPS, which only consists of Na–Ca silicate grains (20 nm). Moreover, as the sintering temperature and dwell time were increased to 700°C and 20 minutes, respectively, a rhenanite‐like phase was also formed (about 15 wt%), other than crystallites growth to 90 nm. Interestingly, the presence of rhenanite provides a beneficial contribution for the production of the HCA layer, which was found the largest for this system when considering storage periods of 7 and 14 days, respectively.